m6A RNA Methylation Regulators Contribute to Malignant Progression and Have Clinical Prognostic Impact in Gastric Cancer - Su, Yunshu; Huang, Jinqi; Hu, Jichang (Frontiers in Oncology, 2019)
m6A is the most common form of mRNA modification, and is dynamically regulated by the m6A RNA methylation regulators. However, little is known about m6A in gastric cancer. The aim of this work is to investigate the effects of m6A RNA methylation regulators in gastric cancer. Here, we found that most of the thirteen main m6A RNA methylation regulators are higher expressed in 375 patients with gastric cancer. We identified two subgroups of gastric cancer (cluster1 and 2) by applying consensus clustering to m6A RNA methylation regulators. Compared with the cluster1 subgroup, the cluster2 subgroup correlates with a poorer prognosis, and most of the thirteen main m6A RNA methylation regulators are higher expressed in cluster2. Moreover, the cancer-specific pathways are also significantly enriched in the cluster2 subgroup. This finding indicates that m6A RNA methylation regulators are closely associated with gastric cancer. Based on this finding, we derived a risk signature, using 3 m6A RNA methylation regulators(FTO, RBM15, ALKBH5), that is not only an independent prognostic marker but can also predict the clinicopathological features of gastric cancer. Moreover, FTO is higher expressed in high risk scores subtype in gastric cancer. Thus, this first finding provide us clues to understand epigenetic modification of RNA in gastric cancer.